Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species - Negrobov, Oleg P.; Grichanov, Igor Ya.; Selivanova, Olga V. (Zootaxa, 2017)
Four new species of Sympycnus Loew, 1857, S. ferganicus sp. nov., S. leleji sp. nov., S. stackelbergi sp. nov. and S. yakutensis sp. nov. from Russia (Yakutia), Kazakhstan, Kyrgyzstan, Tajikistan and Uzbekistan are described. Sympycnus convergens Negrobov, 1973 and S. urgaicus Negrobov, 1973 are placed in synonymy with S. changaicus Negrobov (syn. nov.). Lectotype and paralectotypes are designated for Sympycnus simplicipes Becker, 1908. A checklist of the East Palaearctic species of the genus is compiled and a key to males of the 14 species is provided. Five species groups are defined. New data on the distribution of known species are presented. The known distribution of East Palaearctic Sympycnus species is briefly discussed.